광복 60년 학업중단의 원인,실태,정책의 변화양상과 향후과제 - 박래영; Rae Young Park (청소년복지연구, 2005)
This paper divides the six decades after Restoration of Independence in 1945 into three periods in order to explain the causes, realities, and policies of school dropouts in Korea. The first period, 1945-1980, shows that school dropouts were mainly caused by economic factors. The second period, 1980-1995, reveals that school dropouts were largely due to school factors. The third period, 1996 and after, indicates that school dropouts, according to the Annual Report of Education, have dramatically increased by newly emerging factors. The Korean Ministry of Education has made comprehensive and preventive policies against school dropouts. Previous studies on school dropouts have explained school dropouts solely based on the factors of home, school, and society and suggested policy actions accordingly. But we need a new line of understanding and sufficient social support within a new framework for effective coping with the various needs of school dropouts. A local council for supporting school dropouts is urgently needed to solve out the problems. KCI Citation Count: 19